The prevalence of childhood asthma in white primary schoolchildren in the southern suburbs of Cape Town - Nagel, Frederick Otto (Department of Paediatrics and Child Health, 2018)
The author participated in an international survey organised by the British Medical Research Council (MRC) epidemiological unit in Cardiff, Wales which set out to compare the prevalence of asthma in several countries. The motivation for participating in this study was that very little previous prevalence data for asthma is available for coloured or white children in South Africa. A protocol designed by the British MRC Epidaemiology Unit was followed. One thousand one hundred and seventy four white children aged 12 years attending a random selection of primary schools in the Southern Suburbs of Cape Town were studied. A standard MRC questionnaire on asthma was completed by parents. The subjects then underwent an exercise challenge test (ECT) which involved running on the level for six minutes. During the ECT, we measured the forced expiratory volume in 1 second (FEVl) before and after the exercise. A fall in post exercise FEVl of 15% or greater was regarded as evidence of bronchoconstriction and considered diagnostic of asthma. This method is thought to identify 70-90% of asthmatics (Anderson 1985, Lee et al 1989, Pierson 1988). Using this criterion, 52 (4.4%) of the children had asthma. The prevalence of 4.4% in this study is higher than 3.1% reported in a previous study of black children in Guguletu (Van Niekerk et al, Clinical Allergy 1979). However, the age spectrum of children was different in that study. Terblanche et al (1990) report the prevalence of exercise induced bronchoconstriction (EIB) in white and coloured children to be 5.87% and 4.05% respectively. The level of FEVl reduction for a diagnosis of EIB approved for this study was lower than usually accepted. Using conventional criteria for a diagnosis of EIB, Burr et al (1989) reported a prevalence of 7.7% in Cardiff, Wales. This study confirms that exercise induced asthma is a common problem in 12-year old white children in Cape Town.